2011
DOI: 10.1103/physrevlett.106.175501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of the Formation Mechanism for Pillar Arrays in Nanofilms Subject to Large Thermal Gradients

Abstract: The free surface of molten nanofilms is known to undergo spontaneous formation of periodic protrusions when exposed to a large transverse thermal gradient. Early time measurements of the array pitch and growth rate in polymer melts confirm a formation process based on a long wavelength thermocapillary instability and not electrostatic attraction or acoustic phonon driven growth as previously believed. We find excellent agreement with theoretical predictions provided the nanofilm out-of-plane thermal conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 15 publications
2
62
0
Order By: Relevance
“…Experimental measurements have also confirmed that the characteristic wavelength k o varies strongly with the magnitude of the temperature drop across the bilayer film, DT, essentially ruling out the surface charge mechanism as the dominant source of instability. 16,17 In a previous work, we obtained good functional fits between the experiment and the thermocapillary (TC) model prediction for k o , but close quantitative agreement seemed to require input values of the liquid thermal conductivity many times larger than reported in the literature. We have since revisited our analysis to ascertain whether this problem can be resolved by making improvements to the image analysis in order to extract k o at much earlier times and improvements to the thermal simulations used to assess DT.…”
Section: A Controversy Over the Instability Mechanism In Molten Nanosupporting
confidence: 54%
See 4 more Smart Citations
“…Experimental measurements have also confirmed that the characteristic wavelength k o varies strongly with the magnitude of the temperature drop across the bilayer film, DT, essentially ruling out the surface charge mechanism as the dominant source of instability. 16,17 In a previous work, we obtained good functional fits between the experiment and the thermocapillary (TC) model prediction for k o , but close quantitative agreement seemed to require input values of the liquid thermal conductivity many times larger than reported in the literature. We have since revisited our analysis to ascertain whether this problem can be resolved by making improvements to the image analysis in order to extract k o at much earlier times and improvements to the thermal simulations used to assess DT.…”
Section: A Controversy Over the Instability Mechanism In Molten Nanosupporting
confidence: 54%
“…In this current work, we therefore also show how improved simulations result in revised values of DT which on average are half as large than previously reported. 16 In what follows, we describe the improved image analysis for isolating the fastest growing mode and a more accurate thermal model for assessing the temperature drop across the confined air/nanofilm bilayer. Feature extraction at much earlier times, coupled with more realistic thermal simulations, leads to a better overall functional and quantitative agreement with the thermocapillary model.…”
Section: A Controversy Over the Instability Mechanism In Molten Nanomentioning
confidence: 99%
See 3 more Smart Citations